Pengaruh Pengembangan SDM dan Kepribadian Terhadap Kompetensi dan Prestasi Kerja Karyawan - Irwan Zulkifli (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
In an effort to win the competition, organizations can improve the performance of their employees through developing human resources and their personalities. Therefore, this research aims to analyze the influence of human resource and personality development on employee competence and performance. This research is quantitative research. 150 employees of PT. Millennium Swasindo participated in this research. Data was collected using a questionnaire and analyzed using path analysis processed using AMOS. The research results show that (1) human resource development has a positive effect on competence, (2) personality development has a positive effect on competence, (3) human resource development has a significant positive effect on employee performance, and (4) personality development has a positive effect on performance employee. It is hoped that this research can complement previous research and can be useful for companies in determining policy direction in developing human resources and personalities, and can make companies able to survive in increasingly fierce industrial competition.